Difference and otherness in Husserl’s phenomenology - Rizo-Patrón, Rosemary (Estudios de Filosofía, 2008)
Here I propose to raise some problems of difference and otherness from Husserl’s theory of intersubjectivity. I will not do it, however, from the "reflexive-static" constitutions of the other and the "mundane-genetics" of empathy, the most developed in the well-known Fifth Meditation, which is criticized for supposedly being unable to "overcome the methodological solipsism" of your starting point. Rather, I will address the Husserlian conception of the foundation of social and cultural intersubjectivity, that is, the problems posed at the higher levels of the intermonadic community. Previously, I will review the Husserlian concept of "monad" as a presupposition of the theory of intersubjectivity or "monadology" and I will briefly describe the transcendental articulation of the three intersubjective strata: the pre-reflective or impulsive, the reflective and / or mundane, and the Social. I will see the Husserlian approach to social, active and superior intersubjectivity in correlation with the passive background from which it is constituted: the primary intersubjective intentionality -pre-reflexive, associative, impulsive, affective and carnal.iii Once that is covered basic template, and relying on a posthumous text entitled "Familiar world, strange world, and ’the’ world", I will touch on the properly Husserlian solution to the dilemmas of the dialectic of "unity" versus "multiplicity" and of "identity "versus" difference "under the tense categories of" universal-objective "versus" particular-relative ", and" own "versus" alien "or the" same "versus" other ". [Fragment]